The role of louse-transmitted diseases in historical plague pandemics. Issue 2 (February 2021) - Barbieri, Rémi; Drancourt, Michel; Raoult, Didier
Summary: The rodent-murine ectoparasite-human model of plague transmission does not correspond with historical details around plague pandemics in Europe. New analysis of ancient genomes reveal that Yersinia pestis was unable to be transmitted by rat fleas until around 4000 Before Present, which challenges the rodent-murine ectoparasite-human model of plague transmission and historical details around plague pandemics in Europe. In this Review, we summarise data regarding Y pestis transmission by human lice in the context of genomic evolution and co-transmission of other major epidemic deadly pathogens throughout human history, with the aim of broadening our view of plague transmission. Experimental models support the efficiency of human lice as plague vectors through infected faeces, which suggest that Y pestis could be a louse-borne disease, similar to Borrelia recurrentis, Rickettsia prowazekii, and Bartonella quintana. Studies have shown that louse-borne outbreaks often involve multiple pathogens, and several cases of co-transmission of Y pestis and B quintana have been reported. Furthermore, an exclusive louse-borne bacterium, namely B recurrentis, was found to be circulating in northern Europe during the second plague pandemic (14th–18th century). Current data make it possible to attribute large historical pandemics to multiple bacteria, and suggests that human lice probably played a preponderant role in the interhuman transmission of plague and pathogen co-transmission during previous large epidemics, including plague pandemics.